Assessing the Factors that Influence Family Business Continuity from the Succession Planning Point of View among the Zambian Small and Medium Enterprises - Norah Museta; Mwanza, Bupe Getrude (International Journal of Engineering and Management Research, 2023)
The study’s objective was to assess the factors that influence family business continuity from a succession planning point of view among the Zambian SMEs. Specifically, the study aimed to determine the factors that influence family business continuity from the succession planning perspective and determine the succession planning strategies that can enhance family business continuity. A qualitative research design was employed using purposive and snowball sampling methods to sample 15 family businesses among the SMEs in Chilanga district. Data was collected using one on one interviews using an interview guide. The data was analyzed using a thematic approach. Results of this study show that the factors that influence family business continuity among SMEs include the successor’s level of education, limiting succession to family members, successor’s interest in the business, Successor’s knowledge and skills, mentorship, Successor’s discipline and determination, employee motivation, watching the business closely, the closeness of the family and the profitability of the business. The findings also show that the succession planning strategies used by the family business SMEs to enhance business continuity include; early identification of the successor, choosing successors with a passion and interest for the business, learning from other businesses, gradual handover of the business, training of the successor and involving family and employees in succession planning.